MANAGEMENT OF PANCREATIC PSEUDOCYST - UCHINO, Hirofumi; NAKATA, Toshinori; KUSANO, Toshiomi; MATSUO, Toshikazu; YAMADA, Masafumi; SAKAI, Tsutomu; WATABE, Sei-ichiro; FURUKAWA, Masato; KOGA, Hirotaka; SHIRAKAWA, Kiyoshi (Japanese Journal of National Medical Services, 1992)
Sixteen patients with pancreatic pseudocysts since 1970 were analyzed after dividing them into two groups: a pancreatic group (8 with pancreatitis-associated pseudocyst; P group) and a traumatic group (8 with traumatic pseudocyst; T group). The mean age was younger in the T group (27.8 years) than in the P group (55.1 years). In terms of the male-to-female ratio and the site and morphology of cysts, no differences among two groups were observed. In the P group, 4 patients were treated conservatively, and 4 were treated surgically. In the T group, 5 patients were treated conservatively, and 3 were treated surgically. Of the conservatively-treated patients, US-guided percutaneous pancreatic cyst drainage (PPCD) were performed in 2, percutaneous puncture of the cyst in 1, percutaneous transhepatc bile duct drainage in 1 and medication only in 5. The procedures of surgical treatment were external drainage in 3 patients, the cyst-gastrostomy in 2, the cyst-jejunostomy in 2, and excision of the cyst with distal pancreatectomy in 1. In one patient in which the cyst persisted after external drainage, ethanol injection into the cyst reduced its size. Spontaneous regression of the cyst was observed in 3 patients (18.8%) in the T group. Rupture of the cyst into the peritoneal cavity was observed in 2 patients (12.5%) in the P group and external drainage of the cyst were done. These results indicate the recent increase in conservative treatment (chiefly with US-guided PPCD) for pancreatic pseudocyst and the necessity of considering the risk of spontaneous rupture of the cyst in the management of pancreatic pseudocyst.